Determination of chlorodiazepoxide in pharmacological tablets using high performance liquid chromatography - opposite phase - Zeena Al-Abdaly; Elham Salih (College of Education for Pure Sciences, 2018)
A simple, rapid and sensitive RP-HPLC method has been developed for the determination of chlordiazepoxide on tracer extrasil ODS1 (25mm,0.46mm, 5µm) column using mobile phase consisting of acetonitrile and methanol  (30:70 v/v) at flow rate of 1.0 ml/min and UV detection at 262 nm in 20˚ C. The retention time for chlordiazepoxide was found to be 3.37 min . The  linearity of development method was achieved in the range 5-220 µg/ml with average recovery  101.82% and RSD was less than 3.0%. The method was applied successfully to determine chlordiazepoxide in tablet formulation. Statistical analysis proved that the proposed method was both accurate and precise.